Supercritical CO2 extraction of essential oils from Thymus vulgaris - Melo, Silvio Alexandre Beisl Vieira de (2000)
Supercritical CO2 extraction of essential oil from Thymus vulgaris leaves was studied using experimental data recently obtained in the Florys S.p.A. laboratory. Mass transfer coefficients in the supercritical and solid phases from extraction curves at 40°C and 20 MPa were evaluated using a mathematical model based on the local adsorption equilibrium of essential oil on lipid in leaves. The adsorption equilibrium constant was fitted to these experimental data, and internal and external mass transfer resistances were calculated, allowing identification of the mechanism controlling the extraction process.